The effect of using a low (carbohydrate) diet associated with aerobic exercise in getting rid of obesity (Journal of the College of Basic Education, 2022)
The research aims to set up a program of diet (carbohydrates) and aerobics exercises adapted to the research sample. And know the relationship diet program (carbohydrates) and aerobics in the treatment of obesity research sample. The researchers used the experimental method with one group has been selected sample a deliberate way of women who suffer from obesity and attending Eve center agility and body weight ranging from (75-120) kg of (10) women aged (25-35 years). And the researchers developed two programs, one diet program and the second athlete where it is the first program in the diet (carbohydrates) diet for nine weeks, including three weeks without exercise until the descent of the weight 10 kg and is then aerobics exercise with the diet for 6 weeks. In light of the findings of the researchers was the conclusion: The carbohydrate diet regime has a direct effect on weight loss in conjunction with aerobics exercises by reducing the grease in the various areas of the body as it appeared significant differences in favor of the post test.